Reasons for living, meaning in life, and suicide ideation: investigating the roles of key positive psychological factors in reducing suicide risk in community-residing older adults. (1st February 2016) - Heisel, Marnin J.; Neufeld, Eva; Flett, Gordon L.
Abstract : Objectives: To investigate the roles of reasons for living (RFL) and meaning in life (MIL) in potentially promoting mental health and well-being and protecting against suicide ideation among community-residing older adults and to investigate the psychometric properties of the Reasons for Living Scale-Older Adult version (RFL-OA). Method: Of 173 older adults initially recruited into a longitudinal study on late-life suicide ideation, 109 completed the RFL-OA and measures of cognitive and physical functioning and positive and negative psychological factors at a two-year follow-up assessment. We tested a model in which RFL and MIL protect against suicide ideation, controlling for demographic and clinical factors. We also assessed the psychometric properties of the RFL-OA in community-residing older adults, investigating its internal consistency and its convergent (MIL, perceived social support, and life satisfaction), divergent (loneliness, depressive symptom severity, and suicide ideation), and discriminant validity (cognitive and physical functioning). Results: RFL-OA scores explained significant variance in suicide ideation, controlling for age, sex, depressive symptom severity, and loneliness. MIL explained significant unique variance in suicide ideation, controlling for these factors and RFL, and MIL significantly mediated the association between RFL and suicide ideation. Psychometric analyses indicated strong internal consistency (α = .94), convergent, divergent, and discriminant validity for the RFL-OA relative to positive and negative psychological factors and cognitive and physical functioning. Conclusion: These findings add to a growing body of literature suggesting merit in investigating positive psychological factors together with negative factors when assessing suicide risk and planning psychological services for older adults.